Development and Optimization of Liquisolid Compact Tablet of Ebastine - Dr. Disha Suthar; Jaymina Panthaki; Dr. Shruti Barot; Amar M. Raval; Dr. Khushboo Vaghela (Asian Journal of Pharmaceutical Research and Development, 2026)
Ebastine is a second-generation non-sedating antihistaminic drug indicated for the prevention and treatment of allergic rhinitis and chronic idiopathic urticaria. It is classified under Biopharmaceutical Classification System Class II and exhibits poor aqueous solubility, resulting in dissolution-limited oral absorption. The present work was undertaken to develop and optimize liquisolid compact tablets of Ebastine in order to improve dissolution behavior and pharmaceutical performance. Solubility of Ebastine was evaluated in various non-volatile solvents. Based on maximum drug solubility, Cremophor RH 40 was selected as non-volatile liquid vehicle. Neusilin US2 and Aerosil 200 were selected as carrier and coating materials respectively. Drug-excipient compatibility studies were performed using Fourier Transform Infrared Spectroscopy and Differential Scanning Calorimetry. The formulation was optimized using Design Expert® version 10 software by response surface methodology employing 3² full factorial design. Drug concentration in liquid medication (Cd) and carrier-coating ratio (R) were selected as independent variables, while angle of repose and cumulative percentage drug release at 20 minutes were selected as dependent responses. The optimized formulation was obtained with Cd value of 15.0 and carrier-coating ratio of 26.7. Validation batches confirmed close agreement between predicted and observed values. Crospovidone was selected as suitable superdisintegrant and optimized at 7%. The optimized formulation showed acceptable flow properties and post-compression characteristics. Comparative dissolution study demonstrated faster release than marketed conventional tablet. FTIR studies confirmed compatibility between drug and excipients. DSC and PXRD analysis indicated reduced crystallinity and improved dispersion of drug in final formulation. Accelerated stability study at 40 ±2°C and 75 ±5% RH for one month showed no remarkable change in tablet characteristics. The study confirmed that liquisolid compact technology is a promising and effective approach for enhancing dissolution of poorly water-soluble Ebastine.